Coating containing alumina graft modified silica sol and preparation method thereof

Through the combination of aluminum oxide graft modified silica sol and triazine-based flame retardant, the shortcomings of silica sol coatings in flame retardant and tensile properties are solved, and the excellent performance improvement of the coatings is achieved, which significantly improves its application prospects.

CN119242084APending Publication Date: 2025-01-03SHANDONG KEHAN SILICON SOURCE NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411645533.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing silicon sol coatings have shortcomings in flame retardant and tensile properties, which limit their development in the coating field.

Method used

A combination of alumina graft modified silica sol and triazine-based flame retardant was used to prepare coatings with excellent flame retardant, antibacterial and tensile properties through technical means such as esterification reaction, chain extension reaction and click reaction.

Benefits of technology

The coating has achieved good flame retardant effect, antibacterial performance and tensile performance improvement, significantly improving its application prospects in the coating field.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of silica sol, and discloses a coating containing aluminum oxide graft modified silica sol and a preparation method, and the coating containing the aluminum oxide graft modified silica sol is prepared by reacting the aluminum oxide graft modified silica sol, a triazinyl flame retardant and silica sol. Nitrogen elements in the triazinyl flame retardant and the aluminum oxide graft modified silica sol have a flame-retardant effect, and aluminum oxide groups in the triazinyl flame retardant and sodium sulfonate groups in the triazinyl flame retardant have a relatively good antibacterial effect, so that the synergistic antibacterial effect is achieved; in the stirring process, isocyanate-terminated in the aluminum oxide grafted modified silica sol reacts with hydroxyl in the triazinyl flame retardant, the compatibility of the isocyanate-terminated in the aluminum oxide grafted modified silica sol and the hydroxyl in the triazinyl flame retardant is improved, meanwhile, the isocyanate-terminated in the aluminum oxide grafted modified silica sol and the hydroxyl in the triazinyl flame retardant are wound, so that the coating is denser, and the tensile property of the coating is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silica sol, in particular to a coating containing alumina grafted modified silica sol and a preparation method thereof. Background Art

[0002] Silica sol, also known as silica sol or silica hydrosol, is an excellent nanomaterial widely used in coatings, papermaking, electronics and other fields. In the coating field, silica sol itself does not have a good flame retardant effect, which limits its development. Therefore, how to avoid this phenomenon is the key to solving the problem. For example, patent CN109810631A discloses a water-based organic silicone coating and its preparation method and products. The water-based organic silicone coating has excellent rust-resistant coating performance, and has extremely strong adhesion performance and anti-corrosion and anti-rust performance, and has a wide range of application prospects, but its flame retardant and tensile effects have not been improved. Summary of the invention

[0003] 1. Technical issues to be resolved In view of the deficiencies of the prior art, the present invention provides a coating containing alumina grafted modified silica sol and a preparation method thereof, which has good flame retardant and antibacterial effects and excellent tensile properties.

[0004] (II) Technical solution To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a coating containing alumina grafted modified silica sol, comprising the following components by weight: 6-10 parts by weight of alumina grafted modified silica sol, 5-12 parts by weight of a triazine-based flame retardant, 20-30 parts by weight of silica sol, 1-2 parts by weight of dipropylene glycol butyl ether film-forming aid, 0.2-0.5 parts by weight of a polysiloxane defoamer, 0.4-0.7 parts by weight of an ammonium acrylate wetting agent, 1-2 parts by weight of calcium carbonate, and 12-16 parts by weight of water.

[0005] Preferably, the preparation method of the alumina grafted modified silica sol is: (1) Add aminoacetic acid and silica sol to N,N-dimethylformamide solvent, stir to dissolve, then continue to add p-toluenesulfonic acid catalyst, react at 70-95° C. for 6-10 hours, and then perform vacuum distillation after reaction, filter and dry to obtain amino silica; (2) Add 5-chloro-m-phenylenediamine and amino-silica to the reactor; stir and disperse, then add tripropylamine catalyst, raise the temperature to 75-90°C, reflux for 9-14 hours, cool to room temperature after the reaction, wash with acetone, and obtain a silica chain extender; (3) adding 10-15 parts by weight of hexamethylene diisocyanate and 6-9 parts by weight of polyether polyol to a reaction kettle, and then adding 0.4-0.6 parts by weight of dibutyltin dilaurate, and prepolymerizing under a nitrogen atmosphere for 3-6 hours, and then adding 4-10 parts by weight of a silica chain extender, stirring for 10-15 minutes, and then adding 4-8 parts by weight of amino alumina, reacting for 20-25 minutes, and cooling naturally after the reaction is completed to obtain alumina grafted modified silica; (4) Add 20-30 parts by weight of alumina grafted modified silica, 70-80 parts by weight of water, and 1-2 parts by weight of cellulose ether into a reactor, stir and disperse at high speed, then add 2-3 parts by weight of dodecyl alcohol, 2-4 parts by weight of acrylic emulsion, 1-3 parts by weight of styrene-butadiene emulsion, and 1-2 parts by weight of styrene-acrylic copolymer emulsion, and stir for 50-70 minutes to obtain alumina grafted modified silica sol.

[0006] Preferably, the mass ratio of aminoacetic acid, silica sol and p-toluenesulfonic acid catalyst in (1) is 1.2-1.6:1:0.01-0.03.

[0007] Preferably, the mass ratio of 5-chloro-meta-phenylenediamine, amino-silica and tripropylamine catalyst in (2) is 1:0.8-1.3:0.02-0.04.

[0008] Preferably, the prepolymerization temperature in (3) is 60-85°C.

[0009] Preferably, the preparation method of the triazine-based flame retardant is: S1. Add 5-12 parts by weight of propenyl-1,3-sultone, 15-20 parts by weight of 2-mercapto-1-propanol, and 1-2 parts by weight of dimethylphenylphosphine to N,N-dimethylformamide solvent, introduce nitrogen protection, and heat to 55-80°C, 350-400W / m 2 The reaction was stirred for 2-4 hours under auxiliary light, and after the reaction was completed, the product was distilled under reduced pressure, washed and dried to obtain an intermediate; S2. Add 8-14 parts by weight of the intermediate and 12-16 parts by weight of the silica sol chain extender to an acetone solvent, stir to dissolve, reflux at 75-90°C for 8-15 hours, cool to room temperature, wash and dry, add 3-6 parts by weight of sodium carbonate and water, react at 20-30°C for 5-8 hours, and dry to obtain a triazine-based flame retardant.

[0010] Preferably, the preparation method of the coating containing alumina grafted modified silica is: add alumina grafted modified silica sol, triazine-based flame retardant, silica sol, dipropylene glycol butyl ether film-forming aid, polysiloxane defoaming agent, ammonium acrylate wetting agent, calcium carbonate, and water into a stirrer, stir at room temperature for 10-15 minutes, and then obtain a coating containing alumina grafted modified silica sol.

[0011] 3. Beneficial technical effects The invention adds alumina grafted modified silica sol, triazine-based flame retardant and silica sol into a stirrer, stirs at room temperature, and obtains a coating containing alumina grafted modified silica sol.

[0012] The carboxyl group in aminoacetic acid and the hydroxyl group in silica sol are subjected to esterification reaction to introduce amino groups to obtain amino silica sol, and the chlorine group in 5-chloro-metaphenylenediamine is reacted with the amino group in the amino silica sol to obtain a silica sol chain extender; hexamethylene diisocyanate and polyether polyol are prepolymerized under the action of dibutyltin dilaurate, and the silica sol chain extender and amino alumina are continuously added to react to obtain alumina grafted modified silica sol; the alkenyl group in allyl-1,3-sultone and 2-mercapto-1-propanol are subjected to click reaction to obtain an intermediate (the sulfur element in it will release strong acids such as sulfuric acid when decomposed under high temperature conditions, and the strong acid can promote the dehydration of the substrate into carbon, forming a carbon layer with heat insulation and oxygen isolation effects, slowing down the combustion inside the material, thereby achieving a flame retardant effect), and the sulfonate group of the intermediate is reacted with the amino group in the silica sol chain extender to generate a sodium sulfonate group, thereby obtaining a triazine-based flame retardant.

[0013] The nitrogen element in the triazine-based flame retardant and the alumina-grafted modified silica sol will decompose when heated to generate non-combustible gas, which absorbs heat and isolates oxygen, thereby achieving a flame retardant effect. The alumina group in the triazine-based flame retardant and the sodium sulfonate group in the triazine-based flame retardant have good antibacterial effects and synergistic antibacterial effects. During the stirring process, the terminal isocyanate in the alumina-grafted modified silica sol reacts with the hydroxyl group in the triazine-based flame retardant, which improves the compatibility with each other. At the same time, the two are entangled, making it denser and improving the tensile properties of the coating. DETAILED DESCRIPTION

[0014] 10 g of alumina was ultrasonically dispersed in a mixed solution of anhydrous ethanol and deionized water. After mixing evenly, 30 g of γ-aminopropyltriethoxysilane was added and reacted at 75° C. for 6 h. After the reaction, the mixture was centrifuged, washed, and dried to obtain amino alumina. Example 1

[0015] (1) Adding aminoacetic acid and silica sol to N,N-dimethylformamide solvent, stirring to dissolve, and then continuously adding p-toluenesulfonic acid catalyst thereto, wherein the mass ratio of aminoacetic acid, silica sol, and p-toluenesulfonic acid catalyst is 1.2:1:0.01, reacting at 70° C. for 6 h, and then distilling under reduced pressure, filtering, and drying to obtain amino silica; (2) Add 5-chloro-meta-phenylenediamine and amino-silica to the reactor, stir and disperse, then add tripropylamine catalyst, wherein the mass ratio of 5-chloro-meta-phenylenediamine, amino-silica and tripropylamine catalyst is 1:0.8:0.02, heat to 75°C, reflux for 9 hours, cool to room temperature after the reaction, wash with acetone, and obtain a silica chain extender; (3) 10 parts by weight of hexamethylene diisocyanate and 6 parts by weight of polyether polyol were added to a reactor, and then 0.4 parts by weight of dibutyltin dilaurate were added to carry out prepolymerization under a nitrogen atmosphere at a prepolymerization temperature of 60° C. for 3 hours, and then 4 parts by weight of a silica chain extender were added and stirred for 10 minutes. 4 parts by weight of amino-alumina were added to the reaction mixture and reacted for 20 minutes. After the reaction was completed, the mixture was cooled naturally to obtain alumina-grafted modified silica; (4) Add 20 parts by weight of alumina grafted modified silica, 70 parts by weight of water, and 1 part by weight of cellulose ether to a reactor, stir and disperse at high speed, then add 2 parts by weight of dodecyl alcohol, 2 parts by weight of acrylic emulsion, 1 part by weight of styrene-butadiene emulsion, and 1 part by weight of styrene-acrylic copolymer emulsion, and stir for 50 minutes to obtain alumina grafted modified silica sol; (5) Add 5 parts by weight of propenyl-1,3-sultone, 15 parts by weight of 2-mercapto-1-propanol, and 1 part by weight of dimethylphenylphosphine to N,N-dimethylformamide solvent, introduce nitrogen protection, raise the temperature to 55°C, 350W / m 2 The reaction was stirred for 2 h under auxiliary light, and after the reaction was completed, the product was distilled under reduced pressure, washed and dried to obtain an intermediate; (6) Add 8 parts by weight of the intermediate and 12 parts by weight of a silica sol chain extender to an acetone solvent, stir to dissolve, reflux at 75° C. for 8 hours, cool to room temperature, wash and dry, then add 3 parts by weight of sodium carbonate and water, react at 20° C. for 5 hours, and dry to obtain a triazine-based flame retardant; (7) Add 6 parts by weight of alumina grafted modified silica sol, 5 parts by weight of triazine-based flame retardant, 20 parts by weight of silica sol, 1 part by weight of dipropylene glycol butyl ether film-forming aid, 0.2 parts by weight of polysiloxane defoaming agent, 0.4 parts by weight of ammonium acrylate wetting agent, 1 part by weight of calcium carbonate, and 12 parts by weight of water into a stirrer and stir at room temperature for 10 minutes to obtain a coating containing alumina grafted modified silica sol. Example 2

[0016] (1) Adding aminoacetic acid and silica sol to N,N-dimethylformamide solvent, stirring to dissolve, and then continuously adding p-toluenesulfonic acid catalyst thereto, wherein the mass ratio of aminoacetic acid, silica sol, and p-toluenesulfonic acid catalyst is 1.6:1:0.03, reacting at 95° C. for 10 h, and then distilling under reduced pressure, filtering, and drying to obtain amino silica; (2) Add 5-chloro-meta-phenylenediamine and amino-silica to the reactor; stir and disperse, then add tripropylamine catalyst, wherein the mass ratio of 5-chloro-meta-phenylenediamine, amino-silica and tripropylamine catalyst is 1:1.3:0.04, heat to 90°C, reflux for 14 hours, cool to room temperature after the reaction, wash with acetone, and obtain a silica chain extender; (3) 15 parts by weight of hexamethylene diisocyanate and 9 parts by weight of polyether polyol were added to a reactor, and then 0.6 parts by weight of dibutyltin dilaurate were added to carry out prepolymerization under a nitrogen atmosphere at a prepolymerization temperature of 85° C. for 6 hours. Then 10 parts by weight of a silica chain extender were added and stirred for 15 minutes. Then 8 parts by weight of amino-alumina were added and reacted for 25 minutes. After the reaction was completed, the mixture was cooled naturally to obtain alumina-grafted modified silica. (4) Add 30 parts by weight of alumina grafted modified silica, 80 parts by weight of water, and 2 parts by weight of cellulose ether into a reactor, stir and disperse at high speed, then add 3 parts by weight of dodecyl alcohol, 4 parts by weight of acrylic emulsion, 3 parts by weight of styrene-butadiene emulsion, and 2 parts by weight of styrene-acrylic copolymer emulsion, stir for 70 minutes, and obtain alumina grafted modified silica sol; (5) Add 12 parts by weight of propenyl-1,3-sultone, 20 parts by weight of 2-mercapto-1-propanol, and 2 parts by weight of dimethylphenylphosphine to N,N-dimethylformamide solvent, introduce nitrogen protection, raise the temperature to 80°C, and heat at 400W / m 2 The reaction was stirred for 4 h under auxiliary light, and after the reaction was completed, the intermediate was distilled under reduced pressure, washed and dried; (6) Add 14 parts by weight of the intermediate and 16 parts by weight of a silica sol chain extender to an acetone solvent, stir to dissolve, reflux at 90° C. for 15 hours, cool to room temperature, wash and dry, then add 6 parts by weight of sodium carbonate and water, react at 30° C. for 8 hours, and dry to obtain a triazine-based flame retardant; (7) 10 parts by weight of alumina grafted modified silica sol, 12 parts by weight of a triazine-based flame retardant, 30 parts by weight of silica sol, 2 parts by weight of dipropylene glycol butyl ether film-forming aid, 0.5 parts by weight of polysiloxane defoaming agent, 0.7 parts by weight of ammonium acrylate wetting agent, 2 parts by weight of calcium carbonate, and 16 parts by weight of water are added into a stirrer and stirred at room temperature for 15 minutes to obtain a coating containing alumina grafted modified silica sol. Example 3

[0017] (1) Adding aminoacetic acid and silica sol to N,N-dimethylformamide solvent, stirring to dissolve, and then continuously adding p-toluenesulfonic acid catalyst thereto, wherein the mass ratio of aminoacetic acid, silica sol, and p-toluenesulfonic acid catalyst is 1.4:1:0.02, reacting at 85° C. for 8 h, and then distilling under reduced pressure after the reaction, filtering, and drying to obtain amino silica; (2) Add 5-chloro-meta-phenylenediamine and amino-silica to the reactor; stir and disperse, then add tripropylamine catalyst, wherein the mass ratio of 5-chloro-meta-phenylenediamine, amino-silica and tripropylamine catalyst is 1:1.1:0.03, heat to 82°C, reflux for 21 hours, cool to room temperature after the reaction, wash with acetone, and obtain a silica chain extender; (3) 12 parts by weight of hexamethylene diisocyanate and 7 parts by weight of polyether polyol were added to a reactor, and then 0.5 parts by weight of dibutyltin dilaurate were added to carry out prepolymerization under a nitrogen atmosphere at a prepolymerization temperature of 75° C. for 5 hours. Then 7 parts by weight of a silica chain extender were added and stirred for 12 minutes. 6 parts by weight of amino-modified alumina were added to the reaction mixture and reacted for 22 minutes. After the reaction was completed, the mixture was cooled naturally to obtain alumina-grafted modified silica. (4) Add 25 parts by weight of alumina grafted modified silica, 75 parts by weight of water, and 1 part by weight of cellulose ether to a reactor, stir and disperse at high speed, then add 2 parts by weight of dodecyl alcohol, 3 parts by weight of acrylic emulsion, 2 parts by weight of styrene-butadiene emulsion, and 1 part by weight of styrene-acrylic copolymer emulsion, stir for 60 minutes, and obtain alumina grafted modified silica sol; (5) Add 10 parts by weight of propenyl-1,3-sultone, 15 parts by weight of 2-mercapto-1-propanol, and 1 part by weight of dimethylphenylphosphine to N,N-dimethylformamide solvent, introduce nitrogen protection, raise the temperature to 65°C, 380W / m 2 The reaction was stirred for 3 h under auxiliary light, and after the reaction was completed, the product was distilled under reduced pressure, washed and dried to obtain an intermediate; (6) Add 10 parts by weight of the intermediate and 14 parts by weight of a silica sol chain extender to an acetone solvent, stir to dissolve, reflux at 82° C. for 8-15 hours, cool to room temperature, wash and dry, then add 5 parts by weight of sodium carbonate and water, react at 25° C. for 6 hours, and dry to obtain a triazine-based flame retardant; (7) 8 parts by weight of alumina grafted modified silica sol, 10 parts by weight of triazine-based flame retardant, 25 parts by weight of silica sol, 1.5 parts by weight of dipropylene glycol butyl ether film-forming aid, 0.3 parts by weight of polysiloxane defoaming agent, 0.6 parts by weight of ammonium acrylate wetting agent, 1 part by weight of calcium carbonate, and 14 parts by weight of water are added into a stirrer and stirred at room temperature for 12 minutes to obtain a coating containing alumina grafted modified silica sol. Example 4

[0018] (1) Adding aminoacetic acid and silica sol to N,N-dimethylformamide solvent, stirring to dissolve, and then continuously adding p-toluenesulfonic acid catalyst thereto, wherein the mass ratio of aminoacetic acid, silica sol, and p-toluenesulfonic acid catalyst is 1.2:1:0.01, reacting at 70° C. for 6 h, and then distilling under reduced pressure, filtering, and drying to obtain amino silica; (2) Add 5-chloro-meta-phenylenediamine and amino-silica to the reactor, stir and disperse, then add tripropylamine catalyst, wherein the mass ratio of 5-chloro-meta-phenylenediamine, amino-silica and tripropylamine catalyst is 1:0.8:0.02, heat to 75°C, reflux for 9 hours, cool to room temperature after the reaction, wash with acetone, and obtain a silica chain extender; (3) 15 parts by weight of hexamethylene diisocyanate and 9 parts by weight of polyether polyol were added to a reactor, and then 0.6 parts by weight of dibutyltin dilaurate were added to carry out prepolymerization under a nitrogen atmosphere at a prepolymerization temperature of 85° C. for 6 hours. Then 10 parts by weight of a silica chain extender were added and stirred for 15 minutes. Then 8 parts by weight of amino-alumina were added and reacted for 25 minutes. After the reaction was completed, the mixture was cooled naturally to obtain alumina-grafted modified silica. (4) Add 30 parts by weight of alumina grafted modified silica, 80 parts by weight of water, and 2 parts by weight of cellulose ether into a reactor, stir and disperse at high speed, then add 3 parts by weight of dodecyl alcohol, 4 parts by weight of acrylic emulsion, 3 parts by weight of styrene-butadiene emulsion, and 2 parts by weight of styrene-acrylic copolymer emulsion, stir for 70 minutes, and obtain alumina grafted modified silica sol; (5) Add 10 parts by weight of propenyl-1,3-sultone, 15 parts by weight of 2-mercapto-1-propanol, and 1 part by weight of dimethylphenylphosphine to N,N-dimethylformamide solvent, introduce nitrogen protection, raise the temperature to 65°C, 380W / m 2The reaction was stirred for 3 h under auxiliary light, and after the reaction was completed, the product was distilled under reduced pressure, washed and dried to obtain an intermediate; (6) Add 10 parts by weight of the intermediate and 14 parts by weight of a silica sol chain extender to an acetone solvent, stir to dissolve, reflux at 82° C. for 8-15 hours, cool to room temperature, wash and dry, then add 5 parts by weight of sodium carbonate and water, react at 25° C. for 6 hours, and dry to obtain a triazine-based flame retardant; (7) 8 parts by weight of alumina grafted modified silica sol, 10 parts by weight of triazine-based flame retardant, 25 parts by weight of silica sol, 1.5 parts by weight of dipropylene glycol butyl ether film-forming aid, 0.3 parts by weight of polysiloxane defoaming agent, 0.6 parts by weight of ammonium acrylate wetting agent, 1 part by weight of calcium carbonate, and 14 parts by weight of water are added into a stirrer and stirred at room temperature for 12 minutes to obtain a coating containing alumina grafted modified silica sol.

[0019] Comparative Example 1 The difference between this comparative example and Example 4 is that no alumina graft-modified silica sol is added.

[0020] Comparative Example 2 The difference between this comparative example and Example 4 is that no triazine-based flame retardant is added.

[0021] Performance Testing The limiting oxygen index of the material was tested using an oxygen index meter, and the combustion grade of the coating was tested using a horizontal and vertical combustion instrument. The test results are shown in Table 1.

[0022] Table 1: Flame retardancy tests.

[0023] project Limiting oxygen index (%) Combustion level Example 1 31 V-0 Example 2 33 V-0 Example 3 32 V-0 Example 4 31 V-0 Comparative Example 1 20 V-1 Comparative Example 2 21 V-1 It can be seen from Table 1 that Examples 1-4 of the present invention have better flame retardant effects than Comparative Examples 1-2.

[0024] Tensile properties: Tensile strength and elongation at break were measured according to JIS K6251. The test results are shown in Table 2.

[0025] Table 2: Tensile properties tested.

[0026] project Tensile strength (Mpa) Example 1 12 Example 2 14 Example 3 13 Example 4 12 Comparative Example 1 7.4 Comparative Example 2 6.3 It can be seen from Table 2 that Examples 1-4 of the present invention have better tensile properties than Comparative Examples 1-2.

[0027] Pipette 1 mL of 10 8 CFU / mL of Staphylococcus aureus was added to PBS buffer, and then diluted 10-fold to 10 5CFU / mL, then add the coating sample (1 cm×1cm×0.2mm), and then culture it in a constant temperature incubator at 37℃ with shaking for 24 h. After culture, add PBS buffer to dilute the bacterial solution 10 times in sequence, and then transfer 0.5 mL of the bacterial solution to the agar medium, and continue to culture it at 37℃ with shaking for 24 h. After culture, count the colonies and count the antibacterial rate.

[0028] Table 3: Antibacterial performance test.

[0029] project Antibacterial rate (%) Example 1 98.4 Example 2 99.7 Example 3 98.9 Example 4 99.2 Comparative Example 1 82.4 Comparative Example 2 81.3 It can be seen from Table 3 that Examples 1-4 of the present invention have better antibacterial effects than Comparative Examples 1-2.

[0030] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A coating containing alumina grafted modified silica sol, characterized in that: The invention comprises the following components by weight: 6-10 parts by weight of alumina grafted modified silica sol, 5-12 parts by weight of a triazine-based flame retardant, 20-30 parts by weight of silica sol, 1-2 parts by weight of dipropylene glycol butyl ether film-forming aid, 0.2-0.5 parts by weight of a polysiloxane defoamer, 0.4-0.7 parts by weight of an ammonium acrylate wetting agent, 1-2 parts by weight of calcium carbonate and 12-16 parts by weight of water.

2. The coating containing alumina grafted modified silica sol according to claim 1, characterized in that: The preparation method of the alumina grafted modified silica sol is: (1) Add aminoacetic acid and silica sol to N,N-dimethylformamide solvent, stir to dissolve, then continue to add p-toluenesulfonic acid catalyst, react at 70-95° C. for 6-10 hours, and then perform vacuum distillation after reaction, filter and dry to obtain amino silica; (2) Add 5-chloro-m-phenylenediamine and amino-silica to the reactor; stir and disperse, then add tripropylamine catalyst, raise the temperature to 75-90°C, reflux for 9-14 hours, cool to room temperature after the reaction, wash with acetone, and obtain a silica chain extender; (3) adding 10-15 parts by weight of hexamethylene diisocyanate and 6-9 parts by weight of polyether polyol to a reaction kettle, and then adding 0.4-0.6 parts by weight of dibutyltin dilaurate, and prepolymerizing under a nitrogen atmosphere for 3-6 hours, and then adding 4-10 parts by weight of a silica chain extender, stirring for 10-15 minutes, and then adding 4-8 parts by weight of amino alumina, reacting for 20-25 minutes, and cooling naturally after the reaction is completed to obtain alumina grafted modified silica; (4) Add 20-30 parts by weight of alumina grafted modified silica, 70-80 parts by weight of water, and 1-2 parts by weight of cellulose ether into a reactor, stir and disperse at high speed, then add 2-3 parts by weight of dodecyl alcohol, 2-4 parts by weight of acrylic emulsion, 1-3 parts by weight of styrene-butadiene emulsion, and 1-2 parts by weight of styrene-acrylic copolymer emulsion, and stir for 50-70 minutes to obtain alumina grafted modified silica sol.

3. The coating containing alumina grafted modified silica according to claim 2, characterized in that: The mass ratio of aminoacetic acid, silica sol and p-toluenesulfonic acid catalyst in (1) is 1.2-1.6:1:0.01-0.

03.

4. The coating containing alumina grafted modified silica according to claim 2, characterized in that: The mass ratio of 5-chloro-meta-phenylenediamine, amino-silica and tripropylamine catalyst in (2) is 1:0.8-1.3:0.02-0.

04.

5. The aluminum oxide grafted modified silicon dioxide coating according to claim 2, characterized in that: The prepolymerization temperature in (3) is 60-85°C.

6. The aluminum oxide grafted modified silicon dioxide coating according to claim 1, characterized in that: The preparation method of the triazine-based flame retardant is: S1. Add 5-12 parts by weight of propenyl-1,3-sultone, 15-20 parts by weight of 2-mercapto-1-propanol, and 1-2 parts by weight of dimethylphenylphosphine to N,N-dimethylformamide solvent, introduce nitrogen protection, and heat to 55-80°C, 350-400W / m 2 The reaction was stirred for 2-4 hours under auxiliary light, and after the reaction was completed, the product was distilled under reduced pressure, washed and dried to obtain an intermediate; S2. Add 8-14 parts by weight of the intermediate and 12-16 parts by weight of the silica sol chain extender to an acetone solvent, stir to dissolve, reflux at 75-90°C for 8-15 hours, cool to room temperature, wash and dry, add 3-6 parts by weight of sodium carbonate and water, react at 20-30°C for 5-8 hours, and dry to obtain a triazine-based flame retardant.

7. A method for preparing a coating containing alumina grafted modified silica as claimed in any one of claims 1 to 6, characterized in that: The preparation method of the coating containing alumina grafted modified silica is as follows: adding alumina grafted modified silica sol, triazine-based flame retardant, silica sol, dipropylene glycol butyl ether film-forming aid, polysiloxane defoamer, ammonium acrylate wetting agent, calcium carbonate and water into a stirrer, stirring at room temperature for 10-15 minutes, and then obtaining the coating containing alumina grafted modified silica sol.